PENGARUH MODEL COOPERATIVE LEARNING TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR IPS SISWA DI KELAS V SD NEGERI - sufitri, elsa; Alwi, Elma; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThe purpose of this research is to know the influence of NHT type cooperative learning model on student learning outcomes in social studies subjects. This research is a quasi-experimental research. The research design used is nonequivalent control group design. The sampling technique used is purposive sampling. Based on the results of hypothesis test analysis at 5% significance level obtained t count> ttable (1,798>1,674). The conclusion of this research is the influence of NHT type cooperative learning model to student learning outcomes in IPS subjects.Keywords: Cooperative learning, NHT, learning outcomes